Deep‐UV resonance Raman spectroscopy of hydrated and dehydrated model α‐helical transmembrane peptides in liposomes. (21st September 2021) - Wei, Xing; Jiji, Renee D.; Zare, Anahita; Lada, Bryan; Li, Xiyang; Greenlief, C. Michael
Abstract: Water hydrogen bonding (H‐bonding) to α‐helical transmembrane (TM) peptides is fundamental to better understand the behavior and function of α‐helical peptides, disease pathways, and the development of new drugs. Deep‐UV resonance Raman (dUVRR) spectroscopy is a non‐destructive technique amenable to both lipophilic and aqueous environments, which is an excellent and convenient approach for studying water H‐bonding (or water accessibility) to α‐helical TM peptides in a membrane mimicking environment. The dUVRR results indicate that water molecules can access the lipid membrane and form H‐bonds with carbonyl groups along α‐helical backbones. Raman bands at 1, 629 and 1, 672 cm −1 can be used to monitor the hydration and dehydration conditions along TM α‐helices. Two bands at 1, 300 and 1, 340 cm −1 are also potential characteristic features of the dehydration and hydration along the α‐helices in a membrane environment. Abstract : Deep‐UV resonance Raman (dUVRR) spectroscopy combined with hydrogen‐deuterium exchange are used to investigate potential H‐bonding between model α‐helices and water molecules (or water accessibility) when in a membrane mimicking environment. The dUVRR results indicate that water molecules can access the lipid membrane and form H‐bonds with carbonyl groups along α‐helical backbones. Raman bands at 1, 629 and 1, 672 cm −1 can be used to monitor the hydration and dehydration conditions along transmembrane α‐helices.